Nomophobia! It is necessary to reflect on the question - Pinheiro, Ana Paula; Pinheiro, Fernanda (Anais de Artigos do Seminário Internacional de Pesquisas em Midiatização e Processos Sociais, 2024)
This is a research with a qualitative approach, with analytical-exploratory objectives on the topic of Nomophobia, which has been debated in a naive way since 2008, but intensified with the COVID-19 Pandemic, due to access to devices cell phones, which have become part of the daily lives of the vast majority of the population around the world. In this way, the time spent using devices increased, especially among young people, but not only among them, as children also started using them. Based on the above, this study intended to bring Nomophobia to the academic debate, characterizing and presenting it, so that reflections on preventive measures in relation to this problem can be thought and carried out, as Nomophobia needs to be faced with more seriousness in all contexts, both family, public health, social and educational.